The Palgrave Encyclopedia of American Horror Film Shorts - Rhodes, Gary D. author. aut Link
XVII, 706 p. 71 illus. in color.
Keywords: The Palgrave Encyclopedia of American Horror Film Shorts chronicles for the first time over 1,500 horror and horror-related short subjects theatrically released between 1915, at the dawn of the feature film era when shorts became a differentiated category of cinema, and 1976, when the last of the horror-related shorts were distributed to movie theaters. Individual entries feature plot synopses, cast and crew information, and – where possible – production histories and original critical reviews. A small number of the short subjects catalogued herein are famous; such as those featuring the likes of Buster Keaton, Laurel and Hardy, The Three Stooges, Bugs Bunny, and Daffy Duck; but the bulk are forgotten. The diverse content of these shorts includes ghosts, devils, witches, vampires, skeletons, mad scientists, monsters, hypnotists, gorillas, dinosaurs, and so much more, including relevant nonfiction newsreels. Their rediscovery notably rewritesmany chapters of the history of horror cinema, from increasing our understanding of the sheer number horror films that were produced and viewed by audiences to shedding light on particular subgenres and specific narrative and historical trends. Gary D. Rhodes is Professor of Media at Oklahoma Baptist University, USA. He is the author of numerous books on the cinema, such as The Birth of the American Horror Film (2018), as well as the filmmaker of documentaries, such as Lugosi: Hollywood’s Dracula (1997). David J. Hogan worked for thirty years in Chicago book and magazine publishing as an executive editor and division publisher. He is the author of ten books about various aspects of film, scores of magazine pieces, and essays appearing in numerous cinema monographs. .